2017
DOI: 10.4172/clinical-investigation.1000107
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzymes in patients diagnosed with non-alcoholic fatty liver disease (NAFLD) in Veracruz: a comparative analysis with the literature

Abstract: Background: Up to the present, NAFLD diagnosis has been established through the invasive method of biopsy. The search for a non-invasive alternative, for example biomarkers, is a motive for research. Previous studies have shown that for diabetic or obese patients with NAFLD, the profile of liver enzymes as NAFLD biomarkers has so far not defined pathological liver condition as such. This study aim was comparatively analyze the results of previous research on liver function enzymes of obese patients with NAFLD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Moreover, we evaluated the effect of both HIV infection and genetic factors by conducting a comparison between people living with HIV and Chinese Dai, finding that it increased the chance of the development of MAFLD between 2 and 2.5 times when compared to the genetic factor alone. Moreover, our results agree with previous studies that demonstrated the significant association with PNPLA3 rs738409 and biopsy-proven fibrosis or steatosis among HIV/hepatitis C virus or HBV co-infected patients, HIV-mono infection, and the group with no viral infection[ 33 - 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we evaluated the effect of both HIV infection and genetic factors by conducting a comparison between people living with HIV and Chinese Dai, finding that it increased the chance of the development of MAFLD between 2 and 2.5 times when compared to the genetic factor alone. Moreover, our results agree with previous studies that demonstrated the significant association with PNPLA3 rs738409 and biopsy-proven fibrosis or steatosis among HIV/hepatitis C virus or HBV co-infected patients, HIV-mono infection, and the group with no viral infection[ 33 - 35 ].…”
Section: Discussionsupporting
confidence: 93%
“…Retinoid is primary storage in the liver, about 80% of the total body retinoid stored as retinyl esters in triglyceride-rich lipid droplets in quiescent hepatic stellate cells (HSCs), specialized mesenchymal cells of the liver (30). The HSCs activated and rapidly loss their vitamin A contents in response to liver injury and this process linked to Chronic liver diseases including NAFLD (31,32). It is unclear, the level of hepatic retinoid are reduced in high fat diet, NAFLD (33)(34)(35)(36), and acute liver injury (37).…”
Section: Resultsmentioning
confidence: 99%
“…(5) This disorder is characterized by elevated liver enzyme levels, including higher serum glutamic oxaloacetic transaminase/SGOT (also known as alanine aminotransferase/ALT), serum glutamic pyruvic transaminase/SGPT (also known as aspartate aminotransferase/AST), and alkaline phosphatase (ALP), as well as increased triglyceride and cholesterol levels. (6,7) Higher levels of hepatic enzymes and progressive morphological changes in the liver can lead to irreversible liver disease, such as fibrosis and hepatic cirrhosis. (5,8) Statins are drugs used for hypercholesterolemia that reduce steatohepatitis, but not liver fibrosis.…”
Section: Introductionmentioning
confidence: 99%